Evaluation of Patency of Arteriovenous Fistula and Its Relative Complications in Diabetic Patients - Mortaz, Seyed Saeed; Davati, Ali; Khan Ahmadloo, Maryam; Taheri, Hamid Reza; Golfam, Farzaneh; Tavakoli, Azin; Khalaj, Ali Reza (Urology Journal, 2013)